2019
DOI: 10.1111/jora.12485
|View full text |Cite
|
Sign up to set email alerts
|

Black Adolescents’ Critical Reflection Development: Parents’ Racial Socialization and Attributions About Race Achievement Gaps

Abstract: This research explored the development of Black adolescents’ (N = 454) critical reflection, conceived as individual (i.e., blaming Black people) and structural (i.e., blaming systemic racism) attributions for race achievement gaps. In this longitudinal study, adolescents and their parents reported their individual and structural attributions for race achievement gaps and parents’ racial socialization. Adolescents’ structural attributions increased from Grade 10 to Grade 12. Average levels of individual attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(99 citation statements)
references
References 41 publications
7
83
0
Order By: Relevance
“…Providing opportunities for analysis and reflection on the sources and consequences of social inequalities may help children and adolescents develop a critical understanding of the social, economic, and political systems that they are a part of (Seider et al, 2020). For example, research on family racial-ethnic socialization indicates that conversations about discrimination can contribute to adolescents’ structural explanations for social inequalities (e.g., systemic racism; Bañales et al, 2019). Similarly, research on civic engagement has shown that adolescents who frequently discuss current events with their parents have a better understanding of structural contributors to poverty (Flanagan et al, 2014).…”
Section: Supporting Complex Reasoning About Social Inequalitiesmentioning
confidence: 99%
“…Providing opportunities for analysis and reflection on the sources and consequences of social inequalities may help children and adolescents develop a critical understanding of the social, economic, and political systems that they are a part of (Seider et al, 2020). For example, research on family racial-ethnic socialization indicates that conversations about discrimination can contribute to adolescents’ structural explanations for social inequalities (e.g., systemic racism; Bañales et al, 2019). Similarly, research on civic engagement has shown that adolescents who frequently discuss current events with their parents have a better understanding of structural contributors to poverty (Flanagan et al, 2014).…”
Section: Supporting Complex Reasoning About Social Inequalitiesmentioning
confidence: 99%
“…Parents were not included in the analyses because there was not a valid measure of parental gendered racial socialization at the time of data collection. This decision is also supported by research that finds that youth-reports of socialization are more predictive of youth outcomes (e.g., racial identity and depression) than parent reports (Bañales et al 2020). The adolescent participants ranged in age from 13 to 17 years old (M = 15.4 years; SD = 1.25).…”
Section: Participantsmentioning
confidence: 76%
“…Recently, a growing number of youth development scholars have examined the ways in which critical consciousness can yield positive developmental outcomes, including clearer vocational aspirations (McWhirter & McWhirter, 2016;Olle & Fouad, 2015), improved socioemotional wellbeing (Christens & Peterson, 2012), empowerment (Ballard & Ozer, 2016;Christens et al, 2016;Watts et al, 2011), academic achievement (Seider et al, 2020), and occupational success (Diemer & Blustein, 2006;Diemer et al, 2010). Further, studies have demonstrated a positive association between critical consciousness and contextual factors, such as classrooms that value diversity of thought (Godfrey & Grayman, 2014) and parent and peer socialization related to issues of injustice and oppression (Bañales et al, 2020;Diemer, 2012).…”
Section: Friere Viewed the Relationship Between Reflection And Actionmentioning
confidence: 99%